Analysis of The Effect of Commitment, Motivation And Human Resources Organization of PT. Maha Green - Togar Naibaho; Winfrontstein Naibaho (Institute of Computer Science (IOCS), 2022)
PT Maha Green is a business that is engaged in the distribution of 4 and 3 Kg Elpiji gas to several bases and consumers, but the method used in ordering Elpiji gas is still using the manual method, namely by approaching the bases one by one without knowing how many empty tubes are available at the base to be filled. , so it takes a lot of time. Therefore PT Maha Green is trying to improve services to the Base and Consumers so that the load and time used to deliver orders are more effective. This study aims to determine the effect of motivation and organizational commitment to employee performance at PT.Maha Green. This study uses survey methods and techniques data collection used is a literature study, questionnaires and interviews. The population in this study are all employees of PT. Maha Green totaled 34 people. This research uses the method simple regression analysis and multiple regression. Data that have been collected and processed using the program SPSS 23. The results showed that motivation and organizational commitment has a significant influence on employee performance either partially or partially simultaneous. Organizational motivation and commitment have greater influence on employee performance if both are increased simultaneously rather than simultaneously Partial.